CaCO3 loaded lipid microspheres prepared by the solid-in-oil-in-water emulsions technique with propylene glycol alginate and xanthan gum - Li, Gongwei; Zhao, Yicong; Zhang, Jie; Hao, Jia; Xu, Duoxia; Cao, Yanping (Frontiers in Nutrition, 2022)
Calcium carbonate (CaCO3) is difficult to deliver in food matrices due to its poor solubility. In this work, CaCO3 powders were encapsulated into Solid-in-Oil-in-Water (S/O/W) emulsions to fabricate delivery systems. The impact of Propylene glycol alginate and Xanthan gum (PGA-XG) complexes concentrations on the physical stability and structural characteristics of S/O/W calcium-lipid emulsions microspheres were studied. The S/O/W calcium-lipid emulsions were characterized by the particle size, zeta potential, physical stability, and apparent viscosity. S/O/W calcium-lipid emulsion has higher physical stability (including 6-week storage at 4 °C), smaller mean particle size (7.60 ± 1.10 μm), and higher negative zeta-potential (45.91 ± 0.97 mV) when the PGA-XG complexes concentration was 0.8 wt%. Moreover, Confocal laser scanning microscopy (CLSM) images confirmed that the CaCO3 powders encapsulated on the O phase. Transmission electron microscopy (TEM) showed that S/O/W calcium-lipid emulsion was spherical. X-ray diffraction (XRD) analysis further confirmed that CaCO3 was loaded in the S/O/W calcium-lipid emulsion as an amorphous state. The formation mechanism of S/O/W calcium-lipid microspheres was studied by Fourier transform infrared spectroscopy (FTIR) and Raman spectrum analysis. This study provided new ideas that accelerate the creation of a novel type of calcium preparation with higher quality utilization.